2-Oxoglutarate-dependent dioxygenases in the biosynthesis of simple coumarins - Shimizu, Bun-Ichi (Frontiers in Plant Science, 2014)
Coumarins are natural plant products that have been the subject of extensive phytochemical and pharmacological research studies in the past few decades. The core structure of coumarins, 2H-1-benzopyran-2-one, is derived from the respective cinnamates via ortho-hydroxylation of the aromatic ring, trans/cis isomerization, and lactonization. Various substitution patterns of coumarins have been reported, whereas the biosynthesis of coumarins remains elusive. Ortho-hydroxylation is a key step in simple coumarin biosynthesis as a branch point from the lignin biosynthetic pathway. 2-Oxoglutarate-dependent dioxygenases (2OGDs) from plants convert cinnamate derivatives into simple coumarins through the process of ortho-hydroxylation. This review describes the 2OGDs involved in coumarin biosynthesis and their substrate specificities.